A Review of Endophytic Fungi Bioprospecting in Africa - 1994 to 2014 - Sibanda, Edson P.; Mabandla, Musa; Mduluza, Takafira (Current Biotechnology, 2018)
Background: Despite the recognition that endophytic fungi are an important source of diverse and unique natural bioactive products, there are no reviews outlining how African researchers have been tapping into this bioresource. Objective: This review aims to consolidate and provide insights into the research on fungal endophytes in Africa during the period 1994-2014. Methods: A predefined search protocol was used to undertake a structured search of the bibliographic databases for peer-reviewed research literature. Literature that met the inclusion criteria was then analysed using semi-quantitative and qualitative techniques. Results: One hundred and thirty-nine papers from only 20 African countries met the inclusion criteria, with Egypt (35 papers) and South Africa (31 papers) being the leading countries. The main areas of research were biology and diversity determination (38.1%), bioprospecting for compounds with pharmaceutical potential (35.3%) and assessment of the ability of endophytic fungi to act as biopesticides (21.6%). A diversity of new and known compounds were shown to be secondary metabolites produced by the endophytic fungi and most of these compounds were investigated for their potential as antimicrobial and anticancer agents. Research was observed to have evolved from a focus on endophyte diversity in the 1990s and early 2000s to exploring the possibility of using endophyte fungi as sources of compounds with pharmaceutical and other commercial applications post 2005. Conclusion: In Africa, whilst fungal endophytes remain largely an untapped reservoir of potentially useful natural products, research on the fungal endophytes has also evolved in line with trends elsewhere.
Keywords: fungi